2012
DOI: 10.1038/gim.2012.68
|View full text |Cite
|
Sign up to set email alerts
|

Women’s and health professionals’ preferences for prenatal tests for Down syndrome: a discrete choice experiment to contrast noninvasive prenatal diagnosis with current invasive tests

Abstract: Original research articlePurpose: To compare the preferences of women and health professionals for key attributes of noninvasive prenatal diagnosis for Down syndrome relative to current invasive tests. methods:A questionnaire incorporating a discrete choice experiment was used to obtain participants' stated preference for diagnostic tests that varied according to four attributes: accuracy, time of test, risk of miscarriage, and provision of information about Down syndrome only or Down syndrome and other condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
142
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 39 publications
15
142
3
1
Order By: Relevance
“…13 The attributes cover key differences between NIPT and invasive tests; accuracy, time of test, risk of miscarriage, and type of information. The associated levels reflect current clinically feasible ranges ( Figure 1a).…”
Section: Questionnaire Designmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The attributes cover key differences between NIPT and invasive tests; accuracy, time of test, risk of miscarriage, and type of information. The associated levels reflect current clinically feasible ranges ( Figure 1a).…”
Section: Questionnaire Designmentioning
confidence: 99%
“…9 DCEs have been used to explore preferences for screening and diagnostic tests for DS, looking at attributes such as miscarriage risk, the timing of the test, and the type of information available from test results. [9][10][11][12][13][14][15] Our previous DCE looking at preferences for prenatal tests with reference to NIPT in the United Kingdom demonstrated that HPs placed greater emphasis on test accuracy, while women prioritised test safety. 13 Here we explore women's and HPs' preferences for key attributes of the current DSS and testing pathway and compare these with attitudes towards NIPT in nine culturally diverse countries with differing healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women seem to place more value on the safety of the test and are prepared to wait longer and accept lower accuracy if the test has no risk of miscarriage, whereas healthcare professionals prefer a test that is more accurate. 12 The aim of this study is to further explore women's attitudes and concerns about NIPT and explore their views on widening the scope of prenatal screening through NIPT. Male partners are often not included in research but as decisions about prenatal testing are preferably made by both partners, and research has shown that men want to be involved in this decision-making process, 13 the views of male partners were also explored in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Male partners are often not included in research but as decisions about prenatal testing are preferably made by both partners, and research has shown that men want to be involved in this decision-making process, 13 the views of male partners were also explored in this study. Most studies about pregnant women's attitudes towards NIPT have been based on quantitative methods, 9,10,12,14 which have the advantage of being able to include a large study sample. However, they lack a thorough, in-depth analysis of these attitudes.…”
Section: Introductionmentioning
confidence: 99%